Rare Case of Adult Undifferentiated (Embryonal) Sarcoma of the Liver Treated with Liver Transplantation: Excellent Long-Term Survival - Renumathy Dhanasekaran; Alan Hemming; Elaine Salazar; Roniel Cabrera (Case Reports in Hepatology)
We present the case of a 54-year-old gentleman who presented with abdominal distension and a CT scan of his abdomen revealed a large (25 cm) left hepatic lobe tumor. He received chemotherapy for over 1.5 years. The CT scans at the completion of this therapy revealed that the tumor had actually slightly grown in size. He underwent orthotopic liver transplantation without any major complications. The explant histopathology revealed an undifferentiated embryonal cell sarcoma (UECS) composed of relatively bland spindled cells arranged in short fascicles. It is now 10 years and 3 months since his last transplant and the patient remains well with no tumor recurrence.